PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL INTERAKTIF CANVA PADA MATA PELAJARAN DASAR DASAR PEMASARAN DI SMK NEGERI 15 JAKARTA - Gema Andika Novaldo; Nadya Fadillah Fidhyallah; Kusworo Kusworo (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aimed to develop and evaluate the feasibility of an interactive digital learning media based on Canva for the Fundamentals of Marketing subject at SMK Negeri 15 Jakarta. The study employed the Research and Development (R&D) method using the ADD development model, which consists of three stages: Analisis, Desain, and Development. Data were collected through interviews, observations, expert validation questionnaires (material experts, media experts, and instructional desain experts), and student response questionnaires. The results indicated that the Canva-based interactive digital learning media was successfully developed based on the analisis of teachers' needs and students' characteristics. The developed media includes learning objectives, learning materials, instructional videos, ice-breaking activities, educational games, practice exercises, user instructions, and interactive navigation. The material expert validation obtained an average score of 3.67, categorized as Highly Valid; the media expert validation obtained an average score of 3.58, categorized as Highly Valid; and the instructional desain expert validation obtained an average score of 3.60, also categorized as Highly Valid. Furthermore, the student response questionnaire achieved an average score of 3.61, categorized as Very Good. These findings indicate that the developed media met the material, media, and instructional desain criteria and received positive responses from students. Therefore, the Canva-based interactive digital learning media was deemed feasible for use in teaching the Fundamentals of Marketing subject at SMK Negeri 15 Jakarta.